Assessing the relative impacts of land‐use change and river regulation on Burdekin River (Australia) floodplain wetlands. Issue 10 (1st August 2019) - Tibby, John; Barr, Cameron; Marshall, Jonathan C.; Richards, Jenny; Perna, Colton; Fluin, Jennie; Cadd, Haidee R.
Abstract: The Burdekin River floodplain wetlands are internationally important and act as a sink for sediments and nutrients that would otherwise enter the World Heritage‐listed Great Barrier Reef lagoon. The Burdekin River has the highest natural discharge of any Great Barrier Reef catchment and contributes the greatest mass of sediment to the reef. The river and its catchment have been substantially modified by land clearance, river regulation introduced in the 1960s, the construction of the Burdekin Falls Dam in 1987 and invasive aquatic plants. We hypothesised that the natural variability of Burdekin River discharge would render its wetland ecosystems resistant to human‐induced pressures. Diatoms were analysed from the sediments of two lower Burdekin River floodplain wetlands with contrasting regulation histories. Labatt Lagoon has a long history of flow alteration, whereas Swan's Lagoon has experienced limited regulation. Both wetlands experienced dramatic increases in sedimentation as a result of land clearance, yet the Swan's Lagoon diatom record indicates that the wetland's ecology remains within the range of natural variability. In contrast, Labatt Lagoon is markedly different from its pre‐settlement state. It is now permanent, having been ephemeral for more than 1000 years before European settlement. The conversion to artificial permanence facilitated aquatic plant invasion, resulting in more marked changes than widespread pastoralism. Modern diatom assemblages from 28 lower Burdekin River floodplain wetlands indicate that the contemporary flora of Swan's Lagoon is unusual. Most wetlands have similar assemblages to those in the Labatt Lagoon record in its present, altered state. It is possible, therefore, that the ecological shift registered in Labatt Lagoon is widespread. Diatom records highlight the striking impact that river regulation has had on the trajectory of the Burdekin floodplain wetlands. It is likely that wetland rehabilitation can be facilitated by the re‐introduction of a variable hydrological regime.